In search of reflective techniques in preservice teacher education: Collaboration with parents inspired by school placements - BĄK-ŚREDNICKA, ANNA (Glottodidactica, 2019)
This paper addresses a problem which has been central in teacher education for several decades: how to encourage critical reflectivity in prospective EFL1 teachers. This problem is set within the larger context of the field of school, family and community partnerships. The rationale behind choosing this context is that there is a gap between the significance of various types of such partnerships for the well-being of the whole child, and a lack of deeper understanding of the issue among prospective teachers. The overwhelming majority of research in the matter, conducted mainly in the USA, covers the areas of pre-school, early school and special education (e.g. Lindberg 2014). Additionally, there are few research-based articles related to building the partnership skills of preservice EFL teachers. Therefore, in this paper we attempt to describe the cases of three prospective EFL teachers involved in the process of preparing small scale empirical projects related to the parents’ perspectives. As shown in the paper, engagement in such long term and complex enterprises does not automatically develop the subjects’ deeper understanding of the important role of various types of parent involvement in the (academic) success of children.